2022
DOI: 10.3389/fpsyt.2022.855138
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Telemental Health Care Delivery During COVID-19: A Cross-Sectional Study With Providers, February-March 2021

Abstract: The COVID-19 pandemic accelerated adoption of telemental health (TMH). Providers with limited TMH experience faced challenges during the rapid switch to remote patient care. We investigated TMH providers’ perceptions about remote care one year into the pandemic according to when providers adopted telemedicine (i.e., before vs. after March 2020) and how much of their caseloads were served remotely (i.e., < 50% vs. ≥ 50%). Between February–March 2021, 472 TMH providers completed a cross-sectional, web-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Professionally, most providers were mental health counselors (179/369, 48.5%), psychologists (108/369, 29.3%), or social workers (54/369, 14.6%) working in individual practice settings (279/369, 75.6%) and primarily treating adult patients (18-64 years old; 308/369, 83.5%). More details regarding provider and practice characteristics are reported elsewhere [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Professionally, most providers were mental health counselors (179/369, 48.5%), psychologists (108/369, 29.3%), or social workers (54/369, 14.6%) working in individual practice settings (279/369, 75.6%) and primarily treating adult patients (18-64 years old; 308/369, 83.5%). More details regarding provider and practice characteristics are reported elsewhere [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 495 providers agreed to participate in the study, 369 of whom had complete data for the purposes of this analysis (74.5% completion rate) [36]. The demographic characteristics of providers in the sample were consistent with those of providers in the mental health industry in the United States [13,14,30,34,37,38].…”
Section: Recruitmentmentioning
confidence: 91%
See 1 more Smart Citation
“…There is no information regarding the degree of digital literacy in the study sample although it is characterized by a relatively high degree of education. Previous studies demonstrated that healthcare providers' degrees of experience with digital technologies are associated with the willingness to use these technologies and the way they are judged by their users ( 30 ). Likewise, the acceptance of telemedicine by its users is shaped by the perceived usefulness of the technologies applied, social influence and personal attitude ( 31 ).…”
Section: Limitationsmentioning
confidence: 99%
“…There is no information regarding the degree of digital literacy in the study sample although it is characterized by a relatively high degree of education. Previous studies demonstrated that healthcare providers' degree of experience with digital technologies is associated with the willingness to use these technologies and the way they are judged by their users (28). Likewise, the acceptance of telemedicine by its users is shaped by the perceived usefulness of the technologies applied, social influence and personal attitude (29).…”
Section: Limitationsmentioning
confidence: 99%